A Study of Risk Factors of Stroke in Patients Admitted in Manipal Teaching Hospital, Pokhara. - Maskey, A; Parajuli, M; Kohli, S C (Kathmandu University Medical Journal, 2012)
Background Stroke is usually end result of predisposing conditions that originated years before the ictus. Identification of its modifiable risk factors can help in planning preventive strategies. Objective To study the risk factors of stroke in adult patients. Methods A hospital based prospective cross sectional study was carried out in 160 stroke patients admitted in Manipal Teaching Hospital, Pokhara from November 2007- October 2010. Diagnosis of stroke was confirmed by CT scan of brain. Patients were then investigated for presence of conventional risk factors. The data was statistically analysed using Epi-Info. Results The mean age of stroke patients was 65.98 years ± 10.69 with 126 (78.8%) of patients belonging to age group ? 60 years. It afflicted higher percentage of males 104 (65%) than females 56 (35%). Analysis of stroke subtypes showed preponderance of haemorrhagic stroke in 85 (53.1%) as against infarction in 75 (46.9%) of cases. Other conventional modifiable risk factors were seen as follows: hypertension 98 (61.2 %), cigarette smoking 95 (59.4%), alcohol use 43 (26.9%), left ventricular hypertrophy 44 (27.5%), atrial fibrillation 37(23%), elevated triglyceride 37(23%), diabetes mellitus 15 (9.3%) and elevated total cholesterol 12 (7.5%). Multiple risk factors (? 2) were seen in 122 (76.5 %) cases. Conclusions The maximum occurrence of stroke was seen in patients > 60 years. Overall male preponderance and higher occurrence of haemorrhagic stroke was seen in our study. Significant risk factors in order of descending order were hypertension, cigarette smoking, left ventricular hypertrophy, alcohol use, atrial fibrillation and elevated triglycerides. DOI: http://dx.doi.org/10.3126/kumj.v9i4.6337 Kathmandu Univ Med J 2011;9(4):244-7